Mapping autism in Egypt: population-based insights into prevalence, risk determinants, and severity among children aged 1–12 years - Ammal M. Metwally; Ebtissam M. Salah El-Din; Samia M. Sami; Ehab R. Abdelraouf; Sara F. Sallam; Amal Elsaeid; Mostafa M. El-Saied; Engy A. Ashaat; Asmaa M. Fathy; Hazem M. El-Hariri; Ghada A. Elshaarawy; Maysa S. Nassar; et al. (Molecular Autism)
Abstract Background The prevalence of autism spectrum disorder (ASD), a common developmental disorder, has surged in recent years. Accordingly, the identification and early management of possible risk factors can diminish ASD incidence. Aim To determine the prevalence and severity of idiopathic ASD in Egyptian children aged 12 months to 12 years, and to identify the epidemiological, sociodemographic, and environmental risk factors contributing to this disorder. Methods This study comprised 41,640 children from the main eight geographic areas in Egypt. It was conducted through four phases: household screening, facility-based screening for high-risk children, diagnosis confirmation, and risk factor assessment. Results The prevalence of ASD as confirmed by the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and the Childhood Autism Rating Scale (CARS) was 1.1% (455 out of 41,640), with significant geographic variability. Urban areas had a significantly higher prevalence than rural areas. Children aged 3–6 years showed the highest prevalence at 1.5%. Boys were four times more affected than girls, with prevalence rates of 1.7% and 0.4%, respectively. Significant risk factors included: a history of convulsions (AOR = 4.7; 95% CI: 3.3–6.79), low birth weight (AOR = 2.08; 95% CI: 1.54–2.79), prolonged stays in neonatal intensive care unit (NICU) longer than two days (AOR = 1.91; 95% CI: 1.46–2.49) and maternal health problems during pregnancy (AOR = 1.66; 95% CI:1.36–1.95). Regarding severity, 45% of diagnosed children had moderate ASD, 39% had severe ASD, and 16% had mild ASD. Female gender and older age were significant predictors of greater ASD severity. Conclusion ASD prevalence in Egypt is comparable to other Middle Eastern countries. Policymakers should utilize these findings to design targeted public health interventions aimed at early detection, management, and prevention of ASD progression.